2023
DOI: 10.1084/jem.20221773
|View full text |Cite
|
Sign up to set email alerts
|

Diet-mediated constitutive induction of novel IL-4+ ILC2 cells maintains intestinal homeostasis in mice

Abstract: Group 2 innate lymphoid cells (ILC2s) expressing IL-5 and IL-13 are localized at various mucosal tissues and play critical roles in the induction of type 2 inflammation, response to helminth infection, and tissue repair. Here, we reveal a unique ILC2 subset in the mouse intestine that constitutively expresses IL-4 together with GATA3, ST2, KLRG1, IL-17RB, and IL-5. In this subset, IL-4 expression is regulated by mechanisms similar to but distinct from those observed in T cells and is partly affected by IL-25 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 59 publications
1
0
0
Order By: Relevance
“…Further analysis of 4 Get mice showed that IL4 GFP expression was also detectable in thymic ILC2 (Fig. 7e), consistent with other reports describing ILC2 as a source of type 2 cytokines 26,27 in other tissues. Interestingly, ILC2 were undetectable in the thymus at 1-day post-SLI (Fig.…”
Section: Eosinophil Production Of Il4 Controls Thymus Recovery From D...supporting
confidence: 90%
“…Further analysis of 4 Get mice showed that IL4 GFP expression was also detectable in thymic ILC2 (Fig. 7e), consistent with other reports describing ILC2 as a source of type 2 cytokines 26,27 in other tissues. Interestingly, ILC2 were undetectable in the thymus at 1-day post-SLI (Fig.…”
Section: Eosinophil Production Of Il4 Controls Thymus Recovery From D...supporting
confidence: 90%